Cost-effectiveness of the recombinant zoster vaccine in the German population aged ≥60 years old - Desirée Van Oorschot; Anastassia Anastassopoulou; Barbara Poulsen Nautrup; Lijoy Varghese; Alfred von Krempelhuber; Mohamed Neine; Stéphane Lorenc; Desmond Curran (Taylor & Francis Group, 2019)
Each year, around 300,000 Herpes Zoster (HZ) cases are observed in the German population, resulting in costs over €182 million to society. The objective of this study was to estimate the potential public health and economic impact of the new Adjuvanted Recombinant Zoster Vaccine (RZV, Shingrix) in the German population ≥ 60 years of age (YOA) and to identify the optimal age of vaccination. We used a static, multi-cohort Markov model that followed a hypothetical cohort of 1 million people ≥ 60 YOA life-long after vaccination using German-specific inputs. Both costs and outcomes were discounted at 3%, the incremental cost-effectiveness ratio (ICER) was calculated based on the societal perspective. The coverage of RZV was set at 40% with a second-dose compliance of 70%. Vaccinating the population aged ≥ 60 YOA would result in 45,000 HZ cases avoided, 1,713 quality-adjusted life years (QALYs) gained at a total cost of approximately €63 million compared to 38,000 cases avoided, 1,545 QALYs gained at a total cost of approximately €68 million in the population ≥ 70 YOA. This would result in an ICER of approximately €37,000 and €44,000/QALY, for the age cohort ≥ 60 and ≥ 70 YOA, respectively. Scenario analyses demonstrated that vaccinating at age 60 or 65 YOA would show greater public health impact and would result in the lowest observed ICER compared to vaccinating at 70 YOA. In conclusion, starting vaccination with RZV in the German population ≥ 60 YOA would demonstrate the best value from a public health and economic standpoint.10.1080/21645515.2018.1509645-UF0001